2017
DOI: 10.1159/000470910
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of All-Oral Direct-Acting Antiviral Regimens on the Rate of Development of Hepatocellular Carcinoma in Patients with Hepatitis C Virus Genotype 1-Related Chronic Liver Disease

Abstract: Objectives: There is little information on the risk factors for hepatocellular carcinoma (HCC) and outcome of treatment with an all-oral combination of direct-acting antiviral regimens following eradication of hepatitis C virus (HCV) RNA. Methods: The study subjects were 1,170 patients with HCV genotype 1-related chronic liver disease treated with either NS5A inhibitor plus NS3/4A protease inhibitor (n = 707), NS5A inhibitor plus NS5B polymerase inhibitor (n = 345), or NS5A inhibitor, NS3/4A protease inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…However, it is well documented that treatment with interferon‐based therapies resulted in a reduced incidence of HCC . Furthermore, a recent study by Ogata et al demonstrated through multivariate analysis of 1170 Japanese patients that SVR with DAA therapy, including that of daclatasvir + asunaprevir, sofosbuvir/ledipasvir, and ombitasvir + paritaprevir+ritonavir, was significantly associated with a reduction in the development of HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is well documented that treatment with interferon‐based therapies resulted in a reduced incidence of HCC . Furthermore, a recent study by Ogata et al demonstrated through multivariate analysis of 1170 Japanese patients that SVR with DAA therapy, including that of daclatasvir + asunaprevir, sofosbuvir/ledipasvir, and ombitasvir + paritaprevir+ritonavir, was significantly associated with a reduction in the development of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…At present within Japan, all types of treatment for hepatitis C covered by national insurance are subsidized including interferon‐based and interferon‐free regimens . With this in mind, it has become increasingly essential for patients to seek treatment with DAA's as the cost to patients is quite low; with hepatitis patients generally pay only ¥10 000‐20 000 per month due to heavy subsidies .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that the risk factors of hepatocarcinogenesis after elimination of HCV RNA by direct‐acting antiviral combinations were hypoalbuminemia and high α‐fetoprotein . In the present study, including HCV‐2a/2b patients, multivariate analysis identified an HCV subgroup (HCV‐1b with Gln70(His70)) and age (>65 years) as determinants of hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 49%
“…Our previous study found that the risk factors of hepatocarcinogenesis after elimination of HCV RNA by direct-acting antiviral combinations were hypoalbuminemia and high α-fetoprotein. 26 In the present study, including HCV-2a/2b patients, multivariate analysis identified an HCV subgroup (HCV-1b with Gln70(His70)) and age (>65 years) as determinants of hepatocarcinogenesis. The present study is, to our knowledge, the first report to indicate that aa substitution in the core region also has an association with hepatocarcinogenesis following indirect role in the pathogenesis of HCC.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation